Lingga Isaq Hunting Park as A Basis for Sustainable Management: A Socio-Economic Study - Cut Maila Hanum; Hadi Sukadi Alikodra; Agus Priyono Kartono; Rinekso Soekmadi (Jurnal Manajemen Hutan Tropika, 2018)
The management of conservation and socio economic condition of surrounding communities are always connected each other. The similar case can be found in Lingga Isaq Hunting Park (LIHP), one of the conservation areas located in Aceh Province. This study is aimed to examine socio-economic conditions of the community around LIHP as the basic data to improve the effectiveness of area management. Data were collected through a technical survey by interviewing 120 respondents who were randomly selected from two sub districts namely; Bintang and Linge where each sub district consists of three villages. The results showed that 52.57% of total community income is obtained from coffee plantation which planted within the LIHP area. The level of hunting park contribution to community income, indicates that the communities are highly relies on LIHP area. However, the level of community participation is very low either individually or as a group. The participation is limited to securing and maintaining the area from the forest fires. Local community wisdom is still applied in land clearing and hunting method within the area. Supervision, fostering partnership, relationships between communities and LIHP managers are required to improve community capacity and conservation awareness. As in return, it will reduce community dependence and utilization of LIHP’s land. This study also recommends the need to actively engage with non-governmental organisation or civil society as part of LIHP’s sustainable management. It is intended to improve community welfare and provide opportunities for local wisdom development in the management of LIHP.